Metode Penulisan Kitab Gharib Al-Hadith Serta Pengaruhnya pada Perkembangan Ilmu Hadis - Yasir bin Abdullah (Tadabbur: Jurnal Peradaban Islam, 2020)
The golden age of Islam was in the second and third ages of the Hijri. In that century, Islam had many stories of the greatness of Muslims and treasures of Islam in writing are also very many. One of the most popular Kitabs of the time was Kitab Gharib al-Hadith Abu `Ubayd al-Qasim ibn Sallam al-Harawi. Ulema were amazed because completely contents presenting, so that the Ulema were happy with the Kitab because there’s of what they needed. The Lafaz Gharib Hadiths and it’s explanations is known contens, then how is the method of writing the Kitab Gharib al-Hadith created by Abu `Ubayd al-Qasim bin Sallam al-Harawi? And also, the Kitab is favored by the next Ulema, so how does development influences of the Kitab to the next Gharib al-Hadith? The two big questions will be answered by using descriptive analysis methods in primary data and secondary data. The proces of data analysis uses inductive patterns model. To get answers to these questions, this research by using Library Research. Result the research is that Kitab Gharib al-Hadith created by Abu `Ubayd has the following writing methods : 1. Abwab al-Musnad Method, 2. Naqd al-Sanad Method, 3. Wajiz al-Kitabah Method, 4. Tafsil al-Bayan Method, 5. The Perpose Method on a Hadith, 6. Method of using al-Ma'thur, 7. Method of Using al-Qadaya al-Lughah. In this addition, Abu `Ubayd's Kitab Gharib al-Hadith has a good influence to Ulema who lived with him and after him, among others : there are Ulema who reference the Hadith as Hujjah, there are Ulema who rewrite the Gharib al-Hadith, there are Ulema continue the writing of Gharib al-Hadith, there are the Ulema summarizing the Gharib al-Hadith al-Harawi, there are Ulema who follow the method of writing the Gharib al-Hadith al-Harawi, and there are Ulema who make new methods. In conclusion, Abu `Ubayd's Kitab Gharib al-Hadith has 7 methods in writing. In this addition, this Kitab has a major influence on Islamic treasures, thanks to the Kitab was born other Kitabs both one field and another.